NITRO: a gadget to transform standard rollators into smart rollators for monitoring user conditions. - Ballesteros-Gómez, Joaquín; Fernández-Carmona, Manuel; Urdiales-García, Amalia Cristina (My University, 2023)
The goal of using a rollator is to provide physical stability, support, and increase independence while walking or performing daily activities. The decision to use a rollator is often made in consultation with healthcare professionals, who assess the individual’s mobility limitations and recommend the appropriate assistive device. Rollators can be made “smart” via the inclusion of sensors and actuators, so that they can monitor user condition. This allows caregivers or family members to remotely monitor the user’s condition, track their activities, and receive alerts or notifications if any issues arise. That is particularly important in care home facilities, where the ratio of users per caregiver is high. This work presents the design and initial test of NITRO, a gadget that turNs a rollator Into a smarT ROllator to monitor the user’s gait and routines in care home facilities. Two main requirements have been imposed by the caregivers: first, the gadget should be attached (and detached) to any standard rollator frame (four-wheels, three-wheels, two rear wheels), so users can continue using their rollators: and seconds, it can monitor at any time and anywhere while they use their rollators.
Política de acceso abierto http://biblioteca.cchs.csic.es/registro_buscareditoriales.php?id=828
Keywords: Ortopedia - Innovaciones tecnológicas; Smart rollators; Assitive devices; HealthCare 4.0